Pengaruh Kepuasan Kerja dan Pengawasan Kerja terhadap Kinerja Karyawan Melalui Disiplin Kerja - Anis Fitriya; Kustini Kustini (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This research was conducted with the aim of analyzing the effect of satisfaction, supervision, on performance through the work discipline of CV Andi Jaya employees. The approach used in this research is a quantitative approach. The research population used was all contract employees of CV Andi Jaya with a total of 45 respondents with a saturated sampling technique that made the entire population as a sample in the study. Sources of data used in this analysis is primary data taken directly from contract employees CVAndi Jaya by distributing questionnaires. The source of the data used in this analysis is the data taken directly from employees who in this study are CV Andi Jaya Contract Employees by distributing questionnaires. The results of this study indicate that job satisfaction has no significant effect on work discipline, work supervision has a significant effect on work discipline, job satisfaction and work discipline has an effect on employee performance, work supervision has no effect on employee performance, job satisfaction has no significant effect on employee performance through work discipline and work supervision have a significant effect on performance through work discipline. Keywords: Job Satisfaction, Job Supervision, Employee Performance and Work Discipline